D rn n f r a

Info iconThis preview shows page 1. Sign up to view the full content.

View Full Document Right Arrow Icon
This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: Pn (x) = f (a) + f ′ (a)(x − a) + ÐÐ ×Ø f (n) (a) f ′′ (a) (x − a)2 + · · · + (x − a)n 2! n! ÌÐ Ö ÔÙÒ ØÙÖ n¹Ø Ì ÝÐÓÖ¹Ñ Ö Ð fÑ Ñ Ù aº s Ñ ÐÐ a Ó x ÒÒ En (x) = f (x) − Pn (x) = ÙÑ ×ÚÓ f (n+1) (s) (x − a)n+1 . (n + 1)! f (x) = Pn (x)+En (x) = f (a)+f ′ (a)(x−a)+ ×Ñ Ö ÐÐ f (n) (a) f (n+1) (s) f ′′ (a) (x−a)2 +· · ·+ (x−a)n + (x−a)n+1 , 2! n! (n + 1)! n¹Ø Ì ÝÐÓÖ¹ ÓÖÑ Ð º Ä ØÙÑ ÐÐ º Ë Ð Ö ÒÒ º × ÐÖ Ò ÖÓ ×Ñ f (x, y ) ÚÖ Ò ÐÐ ÒÒ ÝÖ×Ø ×Ø × ÐÙØ ÙÖ f ÖÙ Öº Å Ö Ð P1 (x, y ) = f (a, b) + f1 (a, b)(x − a) + f2 (a, b)(y − b) ÐÐ ×Ø ÝÖ×Ø Ì ÝÐÓÖ¹Ñ Ö Ð Ä ØÙÑ Ò ÖÓ ÖÙ × ÐÖ fÑ f (x, y ) ×Ñ ÐÐ Ñ Ù (a, b)º ÚÖ ÐÐ ÒÒ Ò ÝÖ×Ø Ó ÒÒ Ö× ×Ø × ÐÙØ ¹ Öº Å Ö Ð º Ë Ð Ö ÒÒ º Ð ÙÖ f P2 (x, y ) = f (a, b) + f1 (a, b)(x − a) + f2 (a, b)(y − b) 1 + f11 (a, b)(x − a)2 + 2f12 (a, b)(x − a)(y − b) + f22 (a, b)(y − b)2 2 ÐÐ ×Ø ÒÒÙÖ Ì ÝÐÓÖ¹Ñ Ö Ð fÑ Ñ Ù (a, b)º Ë ÐÖ Ó ÙÑ ×Ø ÔØ Ö Ñ Ð ÒÙÑ ØÚÓ º½¼ Ë Ð Ö Ò Ò Ó ØÙ Ö Ð Ñ ÐÙØ ØÙ ×Ѻ ÙÖ ÙÚ Ö D1 Ó D2 ÒÒ D1 f (a, b) = f1 (a, b) f Ò Ù × Ö ÝØÙº Ð µË ÐÖ D2 f (a, b) = f2 (a, b). ÙÑ Ú ÖÙ ÐÐ Ö × Ö Ö ÐÖ Ð Ò ¸ ÖÓ Ö ×Ñ Ú ÐÐ ÓØ Ö Ö D1 D2 = D2 D 1 ¸ Ø ÐÐ Ø Ø Ð º º º×º ÚÓÖÖ Ö ÙÖ º½½ ÍÔÔÖ ÙÒº ´ÌÚ Ð ÒÙÑ n j ÌÐÒ = n! . j !(n − j )! n+1 n Ð ÒÙ È × Ð×¹ Ö ÝÖÒ Ò × Ò׺ À ÙÑ n j ´Ð × n ÝÖ jµ Ö j+1 ØÐÒ (x + y ) = j =0 n n j xj y n−j . ½ º½¾ Ê Ð º ×Ñ ÐÐ Ö f (x, y ) Ð Ö Ö ÐÐ ÒÒ ÐÐ Ö ÐÙØ ÙÖ n¹Ø Ó Ð Ö ×Ø ÙÑ ÖÙ n (hD1 + kD2 ) f (a, b) = j =0 n n j jn hj k n−j D1 D2 −j f (a, b). º½¿ Ë Ð Ö Ò Ò º ×Ø × ÙÑ ÐÖ Ò ÖÙ × Ñ ÐÐ Ö × ÑÑ Ö Ð ÝÖ Ö Ö Ò ÐÐ n¹Ø Ì ÝÐÓÖ¹Ñ Ö Ð f (x, y ) ÒÒ ÐÐ Ö fÑ ÐÙØ ÑÙ ÙÖ ÔÙÒ Ø ÒÙÑ (a, b) n¹Ø Ó Ð Ö Pn (x, y ) = = 1 ((x − a)D1 + (y − b)D2 )m f (a, b) m! m=0 n m n m=0 j =0 n m 1 m! m j jm D1 D2 −j f (a, b)(x − a)j (y − b)m−j = m=0 j =0 1 jm D1 D2 −j f (a, b)(x − a)j (y − b)m−j . j !(m − j )! ÒÒ ÙÒ Ó ÐÐ Ö ÐÙØ Ö ÙÖ º½ Ë ØÒ Ò º ×Ø ÙÑ ÖÙ × Ñ ½ ÒÒ Ñ ÐÐ ¼ Ó ÝÖ Ö ÐÐ Ö ÐÐ f (x, y ) Ð Ö ÙÑ × n + 1¹Ø ØÐ Ó ÖØ Ð Ð Ö n¹Ø Ì ÝÐÓÖ¹Ò Ð ÙÒ θ h=x−a k =y−b f (x, y ) − Pn (x, y ) = 1 (hD1 + kD2 )n+1 f (a + θh, b + θk ). (n + 1)! º Ò Ö ¾¼½¼ ½ Ê ÒÚ Ð ÙÖ º Å ÐÐ Ö ËØ Ö Ö ½¼º½ Ë Ð Ö Ò Ò º Ë Ë Ø Ø Ö ÒÒ Ö ÒÒ ½¼º ÐÐ ÐÐ Ø ØÚ Ö Ò Ò ÁÁ Ð º Ñ Ö ÝØÙÑ × ÐÖ ÒØ ÑÒ f f ×Ø Ä ØÙÑ ÙÒ f Ð ÚÖ Ð Ð ´ º ÐÓ Ð Ñ Ò ÑÙѵ ÔÙÒ Ø ´ r>0 r>0 f (a, b) ≤ f (x, y ) ×Ø ÙÒ ÝÖ Ö f (a, b) ≥ f (x, y ) ÝÖ Ö Ö × Ñ f Ø ÙÖ ÒÒ ÚÓÖØ ×Ø ÙÒ Ð Ð Ö× Ø f ×Ø ÙÒ Ø Ð ´ º ÐÓ Ð ÜØÖ Ñ µº f (a, b) ≤ f (x, y ) ÝÖ Ö...
View Full Document

Ask a homework question - tutors are online